¡Primeras en organizarse, últimas en la academia! Una aproximación bibliográfica a los sindicatos de trabajadoras del hogar en el Perú - Calderón, Aroma (2020)
This essay offers a bibliographic approach to the study of domestic workers unions in Peru. The relevance of addressing this issue lies in the fact that much of the academic research has focused on highlighting the vulnerabilities of the domestic worker, leaving in the background their ability to organize and transform their working conditions. This vision of domestic workers falls short in the current context, in which the New Domestic Workers' Law has been enacted as a result of the long day of struggle promoted by the same workers. To do this, we present a review of the literature on the historical background of paid work in Peru, trade unions, women's grassroots social organizations, their presence in mixed unions, and, finally, the domestic workers' unions. From this review, we conclude that the absence of bibliography is not only a problem of the academy, but also reveals a profound social problem regarding the conception of domestic workers, which does not end up recognizing their struggle and their role in social change. To fill this gap, it is essential not only to study the unions themselves, but also the antecedents that make it possible for domestic workers unions, made up almost entirely of women, to have an impact on the working conditions of female workers.